Role of Democratic Volunteers as the "Election Marketer" - M. Daimul Abror; Heri Sunarno (Policy & Governance Review, 2018)
Voter turnout in 1999-2009 has decreased significantly. At 1999 92.6% chosen and 7.3% abstains, at 2004 84.1% chosen and 15.9% abstains, at 2009 70.9% chosen and 29.1% abstains. (www.merdeka.com). These conditions encourage Indonesian Election Commision to form Democratic Volunteer as an agent that helps the socialization of Election 2014. This study aims to comprehensively assess the role of Democratic Volunteer as "Election Marketer" in Principal Agency Theory perspective. This study uses qualitative research with case study approach. The results are (1) Relations between Pasuruan Regency Election Commision as principal with Democratic Volunteerasagent (2) Contract model of Democratic Volunteer in two aspects, the type of contract that contract model is short Term Contracts, and the type of both relationship are relation between government and civil society; (3) In carrying out its role as election marketer, Democratic Volunteer fulfill four criteria in Principal Agency Theory perspective. The weakness of model contract of Democratic Volunteer are Short Term Contracts must be solved by entering into a Long Term Contracts to be interwoven communication simultaneously between the government, in this case between Pasuruan Regency Election Commision with Democratic Volunteer as the embodiment of Civil Societies participation is represented by five segments groups of voters.